Formula is Finding Future Value (F) given Gradient Value (G),
Interest (I), and year (N).
F / G: = 1 / N - N / (1 + I)^N - 1
My Problem is when I added value G = 10, I = 10, N =10
I get a result of 93.73 which is wrong. Where i calculate 37.31 as correct.
When I do G =1, I = 10, N = 10.
I get a result of 3.73, which is correct.
Regardless of what I do I can't seem to fix it. Any help and advice is very appreciated. Thank you very much.
Are you quite sure that the answer is not in fact 93.73? And that your formula is truly correct?
Sampson was a strong man who let himself be led astray by a Jezebel, like Delilah. - Pupil's answer to Catholic Elementary School test.
Thank you very much for your response and for your script verification. Now thats an interesting result, it is showing up the same as my scripts. It could very well be possible that this may be an accurate answer. I rechecked my formula in my econ text book. I did made a mistake in my earlier post for it should be A / G instead of F / G. My apologies for this misrepresentation.
it should be this formula, which is identical to my Econ book. So, theoretically it should be correct :/. http://i.ajdesigner.com/d/uniform_gr...s_equation.png
I can't say I am confident on my math skills but this what I got when I calculated manually. So base on my result I was expecting something similar for my script. Unless my calculation and order of operation is flawed.
G = 10 I = 10 / 100 = .10 N = 10
G = (1/.10) - (10 / ((1 + .10)^10) - 1)
My manual calculation and results
A) 1/.10 = 10 Formula - (1/I)
B) 1 + .10 = 1.10 => (1.10)^10 = 2.59 => 2.59 - 1 = 1.59 Formula (1+I)^10 - 1)
C) 10 / 1.59 = 6.28 Formula - 10 / (1+i)^N -1
D) 10 - 6.28 = 3.71 Formula (1/i) - (N / (1 + i)^N -1
E) 10 * 3.71 = 37.10 Formula G *1/i) - (N / (1 + i)^N -1
After all, to transform
Let's just translate that pictured formula, exactly, with no simplifications:
And for G=10, I=10, N=10 indeed I get 37.25
Quite frankly, I don't understand how this:
Also, you are missing the *REQUIRED* parentheses around the sub-expression ( (1+I)^N - 1)
I think the only reason it *SEEMED* to work was because you used the *SAME NUMBER* (10) for both I and N!!!
Wow! Old Pendant, thank your script, this works out beautifully! I spent a couple hours on this, tweak with numerous amount of variation and still couldn't come up with a solution.
A little more tweaking I have to do on my codes and see if I can really understand how this works based on your model.
Once again my appreciation to Old Pendant and Phillip M for your help and feedback. Thank you.
|All times are GMT +1. The time now is 06:16 PM.|
Powered by vBulletin®
Copyright ©2000 - 2013, Jelsoft Enterprises Ltd.